STRATEGI KOMUNIKASI HUMAS KEMENKOMARVES DALAM PEMBERIAN INFORMASI PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT - Menati Fajar Rizki; Muhamad Sabuya (Commed Jurnal Komunikasi dan Media, 2023)
Abstract The Covid-19 pandemic requires the government to impose restrictions on community activities. The purpose of this study was to determine the government's (Coordinating Ministry of Maritime Affairs and Investment) communication strategy for conveying information regarding the Implementation of Restrictions on Community Activities during the Covid-19 pandemic. The theory used is R.Wayne Pace's theory of public relations strategy. This study uses a qualitative research approach with descriptive research methods. Public Relations of the Coordinating Ministry for Maritime Affairs and Fisheries presents data so that the public can understand the current situation and can also comply with the policies made by the government. In The Goals Which the Communicator Sought to Achieve, there are several obstacles that can be overcome, namely data differences with facts in the field, no budget adjustments, and the emergence of hoax news. The conclusion from this research is that the Public Relations of the Coordinating Ministry for Maritime Affairs and Investment has succeeded in carrying out a communication strategy to convey information about PPKM and the Covid-19 pandemic. Keyword: Public Relations; Public Communication; Communication Strategy